Construction of a [Co3(IP)(4,4'-obb)3]n with 4,4'-Oxybisbenzoic Acid and Imidazo[4,5-f][1,10]phenanthroline - Jie Yan, Jing; Cheng, Kai; Qiu, Yue (Asian Journal of Chemistry, 2012)
A new coordination polymer [Co3(IP)(4,4'-obb)3]n (1) (4,4'-obb = 4,4'-oxybisbenzoic acid, IP = 1H-imidazo[4,5-f][1,10]phenanthroline was synthesized and characterized by single-crystal X-ray diffraction, elemental analysis, IR, PXRD. Single-crystal X-ray analyses revealed that [Co3(IP)(4,4'-obb)3]n was bridged by 4'4-obb ligands to form a 1D infinite chain, was further extended to 2D supramolecular structure by hydrogen bonding interactions and p···p interactions.